PHYTOCHEMICAL PROFILE, FABRICATION, AND EVALUATION OF HERBAL TABLETS - DEKA, SURAJ; PRASAD, SURENDER; LALHLENMAWIA, HAUZEL; ROY, PROBIN KR. (International Journal of Current Pharmaceutical Research, 2022)
Objective: The present study investigates the qualitative and quantitative phytoconstituents and to develop and optimize herbal tablets from the methanolic leaves extract of Xanthium indicum J. Koenig ex Roxb and their evaluation. Methods: Preliminary phytochemical screening analyses of methanolic Xanthium Indicum J. leaves extract were determined using standard protocol methods led down in the Pharmacognosy textbook by CK Kokate. In addition, formulation of herbal tablets with sameleaves extracts by wet granulation technique using various concentrations of adsorbent materials such as starch and methylcellulose. Pre-formulation studies such as bulk density, tap density, carr's index, Hausner's ratio, and angle of repose for each formulation were carried out to optimize the flow properties of the granules followed by compression and evaluation of the tablet. Results: The results revealed that methanolic leaves extract of Xanthium indicum J. was found to be the predominant occurrence of phytochemicals such as alkaloids, cardiac glycosides, carbohydrates, flavonoids, phenol, tannins, saponins, terpenoids, amino acids, and carotenoid. The quantitative estimation of bioactive phytoconstituents showed phenolic compounds 285.75±18.24 gm GAE(Gallic acid equivalent)/mg of extract and flavonoids 209.52±20.91 gm QE (Quercetin equivalent)/mg of extract. The optimized formulated herbal tablet was selected as per the evaluation parameter concerning Indian Pharmacopoeia. Conclusion: Methanolic extract of the Xanthium indicum J. leaves holds promises as a potential source of pharmaceutically important phytochemicals and the overall study of the formulated tablets containing plant extract suggests that the optimized formulation is now ready for further preclinical study on animals for its biological activity.